Plate coupling and strain in the far western Aleutian arc modeled from GPS data - Mikhail G. Kogan; Dmitry I. Frolov; Nikolay F. Vasilenko; Jeffrey T. Freymueller; Grigory M. Steblov; Göran Ekström; Nikolay N. Titkov; Alexandr S. Prytkov (Geophysical Research Letters)
Abstract The Aleutian and Kuril‐Kamchatka arcs meet at a triple junction of the Pacific (PAC), Bering (BER), and North American (NAM) plates. We invert GPS observations from the westernmost Aleutian (Komandorsky) Islands and Kamchatka for the fault locking depth and block motion in the far western Aleutian transform boundary. Three boundary models were considered: (1) only the Aleutian thrust fault without a trench‐normal component, (2) only a strike‐slip fault in the back arc north of the Komandorsky Islands, and (3) a rigid Komandorsky sliver bounded by the Aleutian and back‐arc faults. Observed velocities prefer Model 3, with a secular westward sliver velocity of 51 mm/a relative to NAM (two thirds of the total PAC‐NAM motion). The observed velocities are ~10% slower because of elastic strain from boundary faults. The best fitting locking depth of faults bounding the sliver is 12 km, which is similar to depths observed in diverse tectonic environments.